Nafkah Anak Pasca Perceraian menurut Abu Zahrah dan Implikasinya bagi Pelaksanaan Hukum Islam di Indonesia - Udin Safala (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2015)
This paper discusses Abu Zahrah's views on child maintenance after divorce to read critically about the concept in Islamic law in Indonesia. From the exploration of the theoretical framework and library data found, it can be concluded that; First, Abu Zahrah is more likely to use and explore the ideas raised by Abu Hanifah and his followers rather than the ideas of the other three Imam (Malik, Shafi'i, and Ahmad) for reasons not only because the ideas and theories of Abu Hanifah and his followers tend to be moderate when compared to others but also because these ideas are ideal ideas for the sociological society of Egypt at that time; Secondly, child maintenance, in Abu Zahrah's view, is not independently explored because the burden of maintenance is always related not only to children, grandchildren, and so on ('awlad) or vice versa but also relates to hawash which has a relationship with muharramiyah and mawarith kinship which can be operated in various ways.